Morphological Factors Related to Nodal Metastases in Neuroendocrine Tumors of the Appendix: A Multicentric Retrospective Study. Issue 3 (March 2020) - Brighi, Nicole; La Rosa, Stefano; Rossi, Giulio; Grillo, Federica; Pusceddu, Sara; Rinzivillo, Maria; Spada, Francesca; Tafuto, Salvatore; Massironi, Sara; Faggiano, Antongiulio; Antonuzzo, Lorenzo; Santini, Donatella; et al.
Abstract : Objective: The aim of this study was to evaluate clinical and morphological features related to nodal involvement in appendiceal neuroendocrine tumors (NETs), to identify patients who should be referred for oncological radicalization with hemicolectomy. Background: Appendiceal NETs are usually diagnosed accidentally after appendectomy; the indications for right hemicolectomy are currently based on several parameters (ie, tumor size, grading, proliferative index, localization, mesoappendiceal invasion, lymphovascular infiltration). Available guidelines are based on scarce evidence inferred by small, retrospective, single-institution studies, resulting in discordant recommendations. Methods: A retrospective analysis of a prospectively collected database was performed. Patients who underwent surgical resection of appendiceal NETs at 11 tertiary Italian centers, from January 1990 to December 2015, were included. Clinical and morphological data were analyzed to identify factors related to nodal involvement. Results: Four-hundred fifty-seven patients were evaluated, and 435 were finally included and analyzed. Of them, 21 had nodal involvement. Grading G2 [odds ratio (OR) 6.04], lymphovascular infiltration (OR 10.17), size (OR 18.50), and mesoappendiceal invasion (OR 3.63) were related to nodal disease. Receiver operating characteristic curve identified >15.5 mm as the best size cutoff value (area under the curve 0.747). On multivariate analysis, grading G2 (OR 6.98), lymphovascular infiltration (OR 8.63), and size >15.5 mm (OR 35.28) were independently related to nodal involvement. Conclusions: Tumor size >15.5 mm, grading G2, and presence of lymphovascular infiltration are factors independently related to nodal metastases in appendiceal NETs. Presence of ≥1 of these features should be considered an indication for oncological radicalization. Although these results represent the largest study currently available, prospective validation is needed.